Relationships between parental autonomy support, teacher’s autonomy support, self-regulation, and psychological well-being among Iranian adolescents in Kuala Lumpur, Malaysia - Ehsaei, Sara Ghazizadeh (2017)
Decreased psychological well-being is one of the most important issues among adolescents in Iran which also has increased amongst Iranian immigrant adolescents. Many factors are identified as risk and protective factors for adolescents’ psychological well-being. However, very limited research has focused on the role of parental autonomy support and teacher’s autonomy support on psychological well-being particularly among the Iranian adolescents who live in Kuala Lumpur, Malaysia. Therefore, this study aimed to examine the relationships between parental autonomy support and teacher’s autonomy support and psychological well-being. Furthermore, this study examined the role of self-regulation as a mediator for the relationships between the parental autonomy support and teacher’s autonomy support, and psychological well-being. This study utilized the Self-determination theory. Correlational research design was utilized for this study. A total of 170 students aged between 12-18 years old were selected as respondents and the cluster random sampling was employed to obtain the research sample. Respondents selected from one private and two public Iranian schools in Kuala Lumpur, Malaysia. The instruments used for data collection included subjective vitality scale (Ryan and Frederick 1997), Perceptions of Parents Scale (Robbins, 1994), Learning Climate Questionnaire (Williams & Deci, 1996), Academic Self-Regulation Questionnaire (Ryan & Connell, 1989). The results of the Pearson correlation analysis showed a negative significant relationship between age and psychological well-being. Also there was no significant relationship between number of sibling and psychological well-being. However mother’s education, father’s education, family income, parental autonomy support, teacher’s autonomy support were significantly correlated with psychological well-being. In this study, self-regulation mediated the relationship between parental autonomy support, teacher’s autonomy support and psychological well-being among adolescents. The t-test result also indicated that there was no significant difference between males and females in psychological well-being. Hierarchical regression analyses indicated that paternal autonomy support, maternal autonomy support, teacher’s autonomy support and self-regulation were significant contributors to adolescents’ psychological well-being. Moreover, maternal autonomy support was the strongest predictor of adolescent psychological well-being and self-regulation mediated the relationship of parental autonomy support and teacher’s autonomy support with psychological well-being.